2020
DOI: 10.1039/d0gc00544d
|View full text |Cite
|
Sign up to set email alerts
|

Humidity-responsive molecular gate-opening mechanism for gas separation in ultraselective nanocellulose/IL hybrid membranes

Abstract: A class of “green” hybrid membranes composed of nanocellulose and an ionic liquid exhibits exceptional separation properties arising from a humidity-responsive size-exclusive “gate” that allows selective CO2 permeation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…While optimum humidity promotes both CO 2 permeability and selectivity, often exceeding the upper bound Robeson limit, excessive humidity may have an adverse effect on selectivity through relaxation of the polymer network. 548 Using a nanofibrillated cellulose (NFC)-based membrane doped with 1-ethyl-3-methylimidazolium acetate ionic liquid (IL), as shown in Figure 44, Janakiram et al 182 identified three permeation regimes, depending on relative humidity. The first regime (R-I) is dominated by low permeation of semicrystalline NFC nanofibrils because the humidity level is not sufficient to swell the membrane and create continuous water channels.…”
Section: Membranesmentioning
confidence: 99%
“…While optimum humidity promotes both CO 2 permeability and selectivity, often exceeding the upper bound Robeson limit, excessive humidity may have an adverse effect on selectivity through relaxation of the polymer network. 548 Using a nanofibrillated cellulose (NFC)-based membrane doped with 1-ethyl-3-methylimidazolium acetate ionic liquid (IL), as shown in Figure 44, Janakiram et al 182 identified three permeation regimes, depending on relative humidity. The first regime (R-I) is dominated by low permeation of semicrystalline NFC nanofibrils because the humidity level is not sufficient to swell the membrane and create continuous water channels.…”
Section: Membranesmentioning
confidence: 99%
“…94,95 Their inherently high crystallinity and hydrogen-bonding propensity promote the formation of films with excellent gasbarrier properties. 95 Lignin. Lignin is the second-most abundant polymer on Earth after cellulose, serving as structural support to cell walls.…”
Section: Manufacturingmentioning
confidence: 99%
“…Cellulose derives biobased nanomaterialsnamely, nanocellulose, including nanofibrillated cellulose (NFC), cellulose nanocrystal (CNC), and bacterial nanocellulose (BNC)are also emerging green materials for membrane fabrication. , Their inherently high crystallinity and hydrogen-bonding propensity promote the formation of films with excellent gas-barrier properties …”
Section: Biobased Polymers For Membrane Manufacturingmentioning
confidence: 99%
“…9–11 Hence, the fabrication of ionogels for CO 2 separation has received extensive attention from researchers. 12–15…”
Section: Introductionmentioning
confidence: 99%